Antibacterial activity of guava leaf ethanolic extract (Psidium guajava L.) nanosuspension against Escherichia coli bacteria - Nurdianti, Lusi; Yuliana, Anna; Raras, Euis; Setiawan, Fajar; Wulandari, Winda Trisna; Firmansya, Ardianes (Pharmaciana, 2024)
Diarrhea is a condition where a person has bowel movements three or more times a day, with consistent stools. One of the common bacteria that causes diarrhea is Escherichia coli. Empirical and preclinical studies have demonstrated the effectiveness of guava leaves (Psidium guajava L.) in treating diarrhea due to their tannin content. Nanosuspension formulations can be created to simplify the use of guava leaves for medicinal purposes. This study aims to investigate the efficacy of guava leaf extract, both in its natural form and as a nanosuspension preparation, against Escherichia coli. Additionally, the study aims to characterize the guava leaf extract nanosuspension used in the experiment. The technique used to make nanosuspension involves ionic gelation methods by using chitosan as a polymer, and subsequent characterization of the resulting product includes organoleptic testing, specific weight, pH, sedimentation volume, and viscosity. After the characterization of the guava leaf nanosuspension, it was found that the optimal formula had a particle size of 245.7 nm at a concentration of 0.01%, a polydispersion index of 0.406, and a zeta potential of +26.9 mV. Guava leaf ethanol extract 1% has a diameter of the inhibitory zone of 4.05±0.45 mm. However, the nanosuspension form of P. guajava L at a concentration of 0.01% has an inhibitory zone diameter of 11.45±0.64 mm. The nanosuspension formulation using P. guajava L has met the evaluation requirements and has antibacterial activity against E. coli bacteria.